The Journal Human Technology: An Ongoing Resource for Human-Technology Research - Hautamäki, Antti (Human Technology, 2012)
The Agora Center was established in 2002 to provide a platform for interdisciplinary research within the field of human technology. As an independent institute within the University of Jyväskylä, the Agora Center draws together interdisciplinary research teams from a variety of fields, such as information technology, cognitive science, psychology, education, communication, and so on. By establishing international networks and integrating researchers from a variety of countries, the Agora Center team furthers new perspectives on the intersection of humans and technologies. The goal of all of this, then, is to encourage interdisciplinary and intercultural dialogue, cooperation, and collaboration; to encourage and create multiperspective insights and resourcefulness; and to explore creative human-centered solutions to many “wicked problems”: those challenges in life and society that are particularly complex, multifaceted, and require innovative, astute, and productive resolutions.